2016
DOI: 10.1109/lwc.2016.2580669
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Impact of Diffuse Scattering in Urban Millimeter-Wave Deployments

Abstract: In this letter, we characterize the impact of diffuse scattering in dense urban deployments of millimeter-wave (mmWave) systems by using an advanced ray-launching (RL) simulation tool. Specifically, we first construct an RL-based methodology which is well-suited for the proposed analysis, and then investigate the received power distribution both with and without the contribution resultant from the diffuse scattering of rays for both line-of-sight (LOS) and non-LOS (NLOS) conditions. Simulation results are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…This result was somehow unexpected, since previous studies at lower frequencies have highlighted that diffuse scattering is important to model the temporal/angular dispersion characteristics of the channel such as delay spread and angle spread (Fuschini et al, ; Degli‐Esposti et al, ), rather than for PL prediction. Recent studies on outdoor propagation at mm‐wave frequencies have actually shown the importance of nonspecular scattering, but to a lesser extent than what found here (Solomitckii et al, ). It is interesting to note that the shape of the measurement curve is well reproduced by simulations with scattering even where PL is overestimated by simulations.…”
Section: Measurement and Simulation Resultssupporting
confidence: 43%
See 2 more Smart Citations
“…This result was somehow unexpected, since previous studies at lower frequencies have highlighted that diffuse scattering is important to model the temporal/angular dispersion characteristics of the channel such as delay spread and angle spread (Fuschini et al, ; Degli‐Esposti et al, ), rather than for PL prediction. Recent studies on outdoor propagation at mm‐wave frequencies have actually shown the importance of nonspecular scattering, but to a lesser extent than what found here (Solomitckii et al, ). It is interesting to note that the shape of the measurement curve is well reproduced by simulations with scattering even where PL is overestimated by simulations.…”
Section: Measurement and Simulation Resultssupporting
confidence: 43%
“…Connectivity in non‐line‐of‐sight (NLOS) conditions has traditionally relied on multipath propagation, which is nevertheless not as effective at higher frequencies due to lower diffraction effects, and whether mm‐wave communications will work in NLOS conditions in practical deployments still needs to be fully understood. Considerable effort has been spent in recent years in the characterization of mm‐wave propagation, both in indoor (Ai et al, ; Fuschini et al, ; Inomata, Imai, et al, ; Inomata, Sasaki, et al, ; Cheng et al, ; Huang et al, ; Nielsen & Pedersen, ; Karstensen et al, ) and in outdoor scenarios (Rappaport, Xing, et al, ; Sun et al, ; Weiler et al, ; Rappaport, MacCartney, et al, ; Rappaport et al, ; Leonor et al, ; Solomitckii et al, ; Zhong et al, ; Park et al, ; Hur et al, ). Among the latter, some papers are comprehensive surveys on mm‐wave communications (Rappaport, Xing, et al, ) or on mm‐wave propagation models for 5G systems (Rappaport et al, ); others deal with narrowband path‐loss or shadowing models (Rappaport, MacCartney, et al, ; Weiler et al, ) or with wideband mm‐wave models (Rappaport et al, ; Hur et al, ; Park et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, because of the new use cases of wireless systems under the umbrella of 5G and its evolutions, there are several examples in which the propagation conditions may be substantially different to those predicted by state-of-the-art fading models. For instance, in mmWave communications, a scarce number of multipath components arrives at the receiver [28], so that diffuse scattering only becomes relevant when non-line-of-sight (NLoS) conditions are considered [29]. In a different context, the potential of large-intelligent surfaces (LIS) -also, reconfigurable intelligent surfaces (RIS) - [30][31][32][33] to design the amplitude and phases of the scattered waves in order to optimize system performance can also be translated into a superposition of a finite number of individual waves.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable progress has been made in modeling large-scale propagation path loss at mmWave frequencies [4]- [14], and it is well understood that for an assumption of unity gain antennas across all frequencies, Friis equation predicts that path loss is greater at mmWave compared to today's UHF/microwave cellular systems [4]- [6], [8]- [10], [15]. Also, rain and atmospheric attenuation are well understood, and reflection and scattering are more dominant than diffraction at mmWave bands [4], [16]- [19].…”
Section: Introductionmentioning
confidence: 99%